2018
DOI: 10.1111/ddi.12870
|View full text |Cite
|
Sign up to set email alerts
|

Decadal effects of landscape‐wide enrichment of dead wood on saproxylic organisms in beech forests of different historic management intensity

Abstract: Aim European temperate forests have lost dead wood and the associated biodiversity owing to intensive management over centuries. Nowadays, some of these forests are being restored by enrichment with dead wood, but mostly only at stand scales. Here, we investigated effects of a seminal dead‐wood enrichment strategy on saproxylic organisms at the landscape scale. Location Temperate European beech forest in southern Germany. Methods In a before–after control–impact design, we compared assemblages and gamma divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
24
0
1
Order By: Relevance
“…bryophytes (Heilmann-Clausen et al 2005). This might be explained by strong competition between fungi in single dead wood pieces, with the consequence that only a few species build fruiting bodies (Heilmann-Clausen and Christensen 2004;Fukami et al 2010;Roth et al 2019). Probably due to these processes, other studies on wood-inhabiting fungi likewise did not show a relationship between local dead wood amount and community composition (Krah et al 2018) or changes in composition 10 years after dead wood enrichment (Roth et al 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…bryophytes (Heilmann-Clausen et al 2005). This might be explained by strong competition between fungi in single dead wood pieces, with the consequence that only a few species build fruiting bodies (Heilmann-Clausen and Christensen 2004;Fukami et al 2010;Roth et al 2019). Probably due to these processes, other studies on wood-inhabiting fungi likewise did not show a relationship between local dead wood amount and community composition (Krah et al 2018) or changes in composition 10 years after dead wood enrichment (Roth et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…This might be explained by strong competition between fungi in single dead wood pieces, with the consequence that only a few species build fruiting bodies (Heilmann-Clausen and Christensen 2004;Fukami et al 2010;Roth et al 2019). Probably due to these processes, other studies on wood-inhabiting fungi likewise did not show a relationship between local dead wood amount and community composition (Krah et al 2018) or changes in composition 10 years after dead wood enrichment (Roth et al 2019). In contrast, Raabe et al (2010) found an effect of local dead wood amount on the community composition of epixylic bryophytes, and the models they used managed to explain 21% of the variance, a value our models did not reach.…”
Section: Discussionmentioning
confidence: 99%
“…Active enrichment entails leaving parts of trees such as crowns or stem sections within harvest units [84]. Active enrichment has been found to increase deadwood amounts on the landscape level in young and formerly managed forests, thus enhancing biodiversity [85]. Other strategies involve the use of explosives and partial cutting of tree crowns [86].…”
Section: Strategies For Achieving Ecologically Sustainable Managementmentioning
confidence: 99%
“…Lindenmayer 2017; Prevedello et al 2018) and dead wood (e.g. Roth et al 2018) to biodiversity, but more specific insights into their role in retention systems in temperate forests are limited (but see Vítková et al 2018; Asbeck et al 2019). Largely independent of the silvicultural system, studies from European forests have indicated that trees serving conservation purposes can improve biodiversity by increasing habitat diversity (Müller et al 2014; Gutzat and Dormann 2018), and that the abundance of tree-related microhabitats (e.g.…”
Section: Retention Elements and Biodiversitymentioning
confidence: 99%